Glycation of LDL: AGEs, impact on lipoprotein function, and involvement in atherosclerosis - Poznyak, Anastasia V.; Sukhorukov, Vasily N.; Surkova, Raisa; Orekhov, Nikolay A.; Orekhov, Alexander N. (Frontiers in Cardiovascular Medicine, 2023)
Atherosclerosis is a complex disease, and there are many factors that influence its development and the course of the disease. A deep understanding of the pathological mechanisms underlying atherogenesis is needed to develop optimal therapeutic strategies and treatments. In this review, we have focused on low density lipoproteins. According to multiple studies, their atherogenic properties are associated with multiple modifications of lipid particles. One of these modifications is Glycation. We considered aspects related to the formation of modified particles, as well as the influence of modification on their functioning. We paid special attention to atherogenicity and the role of glycated LDL in atherosclerosis.